(untitled) (Fiep Bulletin - online, 2014)
The specific footwear is an important instrument for soccer players. For this reason those footwear should be made respecting the characteristics of the foot of each athlete, providing comfort for them. The aim of this study is to describe the foot-footwear comfort’s main pointers in athletes of base categories of soccer, as well as evaluating the satisfaction level of the athletes for the footwear used in their practice and verifying the athletes’ level of perception in relation to the comfort of footwear. This research is characterized as being an observational descriptive study in a quantitative paradigm. The study was conducted with 15 male soccer athletes of base categories of a soccer club, between 15 and 21 years of age. The instruments used for this research were one interview with personal data of the athletes and the footwear utilized during the sportive practice, one questionnaire of the athlete’s satisfaction level for the footwear used in their practice and the adapted table for the level of perception in relation to the comfort of footwear, elaborated according to the Brazilian Association of Technical Norms (ABNT) - NBR 14840, of March 2002. Through this instruments, it was observed that the majority of the athletes consider the footwear used on the sportive practice comfortable, being satisfied with them. All the items studied had demonstrated that, to obtain a comfortable sportive footwear, it is necessary not just the specific footwear for that kind of sport, but, also, adequate it to the individual perception of comfort. And, on this way, guaranteeing the athletes satisfaction.